Exploring Teachers’ Professional Development Based on Pedagogical Content Knowledge: A Case of in-Service Biology Teachers in Tanzania - Mateka, Hassan A.; Magambo , Neema; Rembesha, Medard (Journal of Education and Practice, 2024)
Purpose: This study aimed to reveal the impact of the professional development program on the enhancement of pedagogical content knowledge (PCK) among in-service biology teachers. Instructional strategies, students' misconceptions and learning difficulties, representation of the content, context for learning, and curriculum knowledge were some of the main PCK themes. Methodology: Eighteen secondary school teachers from six regions in Tanzania were involved in the intervention program. The study adopted a mixed-methods and case-study research design to collect both quantitative and qualitative data. Findings: The study revealed a positive transformation in the teachers’ conception of teaching and learning processes by shifting from a traditional teacher-centred approach to a more constructivist approach. Teachers are competent with the new trends in teaching and learning biology, including the use of technology and improved instructional materials, utilization of the local environment, and integrating academic content knowledge with everyday life. Unique contribution to theory, practice and policy: Based on the findings, it is recommended that in-service teachers' professional development programs be an ongoing process with the ultimate goal of offering opportunities to learn contemporary teaching methods, improve teaching skills, and acquire a broad knowledge of how students learn biology.